Avaliação da atividade antioxidante e bioacessibilidade de compostos fenólicos em diferentes espécies de flores comestíveis - Morais, Janne Santos de (2020)
The use of flowers as ingredients in gourmet cuisine is increasing due to the exotic characteristics that confer to foods and drinks. Among the edible flowers, mini rose and mini daisy stand out for their delicate appearance, begonia and tagete for their citrus flavor, clitoria for their vibrant color, cravine for their spicy flavor and torenia for their velvety texture. Edible flowers have antioxidants, which can benefit consumers' health. The objective of this study was to evaluate antioxidant activity and bioaccessibility of phenolic compounds from eight species of edible flowers, namely in mini rose, torenia, mini daisy, clitoria, cosmos, cravine, begonia e tagete. The bioaccessibility of phenolics present in flowers was determined using an in vitro digestion system coupled to a simulated intestinal barrier. The antioxidant activity of flowers before in vitro digestion, and their dialyzed and non-dialyzed fractions, was evaluated by the ability to remove the radicals 2,2-diphenyl-2-picrilhidrazide hydrate (DPPH•), ferric reducing antioxidant power (FRAP) and Oxygen radical absorption capacity (ORAC). All evaluated flowers presented in their composition phenolic acids, stilbenes, flavanols, anthocyanins, flavonols and flavanones, but different compounds and quantities were found in each flower. Cosmos presented highest (p < 0.05) contents of phenolics, flavanones and stilbenes, being hesperidin and trans-resveratrol, the main compounds detected in this flower. In contrast, tagete presented lowest (p < 0.05) contents of phenolics, flavonols and anthocyanins. Bioaccessibility varied among phenolic and between flowers studied (p < 0.05). The highest (p < 0.05) bioaccessibility was found in the cosmos that presented the larger amounts of flavanols and flavonols in the dialyzed fraction, primarily catechin and quercetin 3-glucoside compounds. The lowest (p < 0.05) total bioaccessibility was found in mini rose, while torenia displayed the lowest (p < 0.05) bioaccessibility of the flavonols. Several compounds were detected in the non-dialyzed fraction of the evaluated flowers, with the highest (p < 0.05) and lowest (p < 0.05) contents in the cravine and tagete, respectively. Cosmos showed the highest (p < 0.05) antioxidant activity in the ORAC assay before in vitro digestion and in dialyzed and non-dialyzed fractions; the observed activity was correlated (r = 0.9) to its major compounds hesperidin and rutin, as well as to caffeic acid and procyanidin B2. Mini rose presented highest (p < 0.05) antioxidant activity in FRAP and DPPH assays before in vitro digestion; its dialyzed and non-dialyzed fraction showed the highest (p < 0.05) activity in FRAP, which was correlated with the compounds pelargonidine 3,5-diglucoside, catechin, epicatechin gallate, epicagocatechin gallate, procyanidin A2, quercitin 3-glucoside and trans-reveratrol (r = 0.9). In the DPPH assay, mini rose showed the highest (p < 0.05) activity in the non-dialyzed fraction, while cravine showed the highest (p < 0.05) activity in the dialyzed fraction, which was mainly correlated with sirinic acid (r = 1.0), 3,5-diglucoside pelargonidine. and epicatechin (r = 0.9). The results show variability in phenolic composition and its bioaccessibility among the edible flowers studied. The cosmos and mini rose flowers are suggested because they have bioaccessible phenolics with high antioxidant activity.